Mapping propagation of collective modes in Bi2Se3 and Bi2Te2.2Se0.8 topological insulators by near-field terahertz nanoscopy - Eva Arianna Aurelia Pogna (Nature Portfolio, 2021)
Propagation of photoexcited modes provides important information for novel quantum state. Here, the authors reveal the propagation of sub-diffractional hyperbolic phonon-polariton modes influenced by the Dirac plasmons in topological insulators.